Meloidogyne inornata em feijoeiro: aspectos biológicos e reação de cultivares - Dadazio, Tais Santo [UNESP] (2015)
The culture of the bean has its limited productivity by biotic factors, such as plant parasitic nematodes. Several species have been reported causing damage to the culture, especially those belonging to the genus Meloidogyne. Recently, a new species was reported parasite culture in State of Paraná, M. inornata. Due to this report, the present study aimed to generate information about its life cycle and feeding sites under different temperatures, compared to M. incognita, characterize the resistance reaction of 32 bean cultivars M. inornata and check the potential damage of this nematode. The reaction test was conducted in a greenhouse, and inoculated 2,000 eggs / plant. After 50 days, it was found that all cultivars susceptible behaved as against nematodes, with RF ranging from 13.69 to 94.71 for the color group and 17.31 to 80.46 for the group black. The damage level experiment was also carried out in a greenhouse, the inoculation of the following population densities of M. inornata in bean cv. Tuiuiú: 0 (control); 0.0625; 0.125; 0.25; 0.5; 1; 2; 4; 16; 32; and 64 eggs per cm3 of soil. The tolerance limit set for cultivating Tuiuiú inoculated with M. inornata was 9.9 cm3 of soil nematodes, that is, from that population density the plant becomes damaged by nematodes. Regarding the comparative biology of M. inornata with M. incognita, the experiments were conducted in a growth chamber type BOD at temperatures of 18 ° C, 25 ° C and 32 ° C. The results showed that at a temperature of 25 ° C is optimal for the development of both species, while at 18 ° C, the cycle of both species is retarded and 32 ° C, the cycle is accelerated; Furthermore, both species formed a similar permanent feeding site.